Dominasi Asas Lex Specialis dalam penyelesaian wanprestasi pada lembaga keuangan syariah - viona, amanah giovani visi yuti; anwar, khoirul anwar; Fadhl, Sarah Ummu Fadhl; Imami, Ainaya Harisa Imami (Maliki Interdisciplinary Journal, 2026)
This study investigates the influence of lex specialis derogat legi generali in resolving defaults in Islamic financial institutions in Indonesia. This research is based on the growing practice of Islamic transactions, which demonstrates the need for legal certainty to resolve disputes arising from defaults. The lex specialis principle is applied to determine the relevant law compared to general civil law. Normative legal research is conducted through statutory and conceptual methods, coupled with qualitative analysis of primary and secondary legal sources. The findings of this study indicate that, from both the perspective of judicial power and the content of the law applied, the lex specialis principle plays a significant role in resolving Islamic economic conflicts. In resolving cases related to Islamic economics, religious courts apply principles derived from Islam as well as relevant specific rules. In conclusion, Islamic economic law, as a specialized law, provides better legal certainty than general civil law in resolving defaults. However, a greater understanding of the regulations and better coordination are needed for optimal implementation.